Gallbladder carcinoma: An analysis of the national cancer data base to examine hispanic influence. Issue 8 (1st May 2018) - Liu, Chrissy; Berger, Nicholas G.; Rein, Lisa; Tarima, Sergey; Clarke, Callisia; Mogal, Harveshp; Christians, Kathleen K.; Tsai, Susan; Gamblin, T. Clark
Abstract : Background: Gallbladder cancer (GBC) is a lethal disease with high incidence among Hispanics. Overall survival (OS) among races/ethnicities has not been described using the most recent National Cancer Database. This study hypothesized that prognosis is worse for Hispanics compared to similar non‐Hispanic populations. Methods: Patients with GBC were identified from the National Cancer Database and categorized as White, Black, Hispanic, and Other. Descriptive statistics, OS, and Cox regression were examined. Results: The study identified 12 952 patients. Median age was 71 years and 68.8% were female. The study characterized 69.8% White, 13.9% Black, 11.0% Hispanic, and 5.4% other patients. A 5‐year OS curves differed, with survival highest in Hispanic patients (27% vs 23% Other, 18% White, and 17% Black, P < 0.001). Hispanics presented at younger ages (67 vs 72 years, P < 0.001), were more likely to be uninsured (17.3% vs 3.9% P < 0.001), had lower income ( P < 0.001), and education levels ( P < 0.001) compared to Whites. Following multivariable modeling, treatment at an academic facility (HR 0.90, 95%CI 0.84‐0.97) and year of diagnosis (HR 0.90, 95%CI 0.88‐0.92) related to survival. Hispanic ethnicity did not show significance ( P = 0.207). Discussion: Hispanic ethnicity exhibits the highest OS for GBC, but after adjusting for covariates, this influence is not significant.